Hibridação de palmeiras “Bacabas” (Oenocarpus spp., Arecaceae) em sistemas agroflorestais na região do Pedral do Lourenço do Pará - Rech, Luiz Renato Santos (2022)
The economic potential of palm trees of the genus Oenocarpus and the search for the process of domestication of the same, justifies the interest in understanding the hybridization phenomenon for being of great evolutionary interest, as well as defining the origin and genetic composition of the hybrids and their viability. , in addition to verifying the reproductive barriers between the hybrid and its parents. This thesis aims to test the hypothesis of a hybrid origin of Oenocarpus x, evaluating its phylogenetic position, in addition to its relationships with the species considered putative parental (Oenocarpus mapora X Oenocarpus distichus). Furthermore, to investigate cytogenetic aspects, genomic size, reproductive behavior and morphological descriptors of the species, confronting the speciation hypothesis. Nine accessions of the genus Oenocarpus were selected for research, both with 12 years of age and conducted in agroforestry systems, 04 belonging to the species Oenocarpus mapora, 04 belonging to the species Oenocarpus distichus and 01 interspecific hybrid Oenocarpus x. The 16 morphological descriptors considered in the analysis of phenotypic diversity of the aforementioned accessions followed the methodology used in data collection adapted from Oliveira et al., (2007). In the statistical analyses, the computational resources of the Excel Program were used, where the data were tabulated, and the Genes Program, where the data were analyzed. To assess reproductive viability, it is through the monitoring of phenological events that is based on the characterization of phenophases and their intensity. The most frequent phenophases were the emission of bracts, flowering inflorescences and bunches with immature fruits. The flowering peak occurred from May to November, coinciding with the period of lowest rainfall in the region, and fruiting occurred practically every month of the year. During the 03 production cycles, the hybrid palm did not present bunches with ripe fruits, only the formation of frutillos that undergo abortion before the final phenological stage. The interspecific hybrid Oenocarpus x managed to overcome the first and second reproductive barriers, pollination and pre-zygotic, respectively. The descriptors that presented the highest coefficient of variation were the number of leaves with 20.41% and the number of leaflets. The genetic distance based on the square Euclidean distance of the evaluated characters of Bacabas palms ranged from 24.92 to 42.81. Regarding the relative and accumulated variances of the characters by the analysis of principal components, it was found that 97.8% of the variation was explained by the characters x15 (length of the rachilla (cm)), with 36.38% of the variation, followed by x10 (length of five internodes (cm)), x11 (height of the first bunch), x13 (length of the rachis of the bunch (cm)), x14 (number of rachillas per bunch (n)) with 17.8%, 15.40%, 14.10% and 14.20% respectively of the percentage of divergence. It is concluded that Oenocarpus x has morphological characteristics that are intermediate between the palms of the species O. mapora and O. distichus, which reinforces the occurrence of interspecific hybridization. It can also be concluded that, despite the non-maturation of the fruits of Oenocarpus x, it shows great productive potential, as it has a smaller size, a desired characteristic for harvesting, a greater length of the rachilla, which confers a greater capacity for fruit production and greater number of inflorescences per year.